Micron- to atomic-scale investigation of rare earth elements in iron oxides - Cook, Nigel J.; Ciobanu, Cristiana L.; Ehrig, Kathy; Slattery, Ashley D.; Gilbert, Sarah E. (Frontiers in Earth Science, 2022)
Hematite (α-Fe2O3) and magnetite (Fe3O4) readily accommodate a wide range of minor and trace elements from across the periodic table at up to wt.% concentrations. This prompts the question of whether these common minerals can also host rare earth elements (lanthanides, Y and Sc; REEs)? If so, what is the chemical and physical nature of the elements: are they incorporated into the oxide crystal structures, or do they occur as nanometer- to micron-sized inclusions of discrete REE-minerals? By combining micron-scale petrography and analysis by LA-ICP-MS with nanoscale imaging and energy-dispersive spectroscopy, the relationships between REE and iron-oxides are addressed in samples from the world-class Olympic Dam Cu-U-Au-Ag deposit, South Australia. Spatially co-existing silician magnetite and hematite from the outer shell at Olympic Dam show stages of interconversion during which REE are redistributed. REE are shown to be preferentially incorporated into the magnetite structure, whereas hematite concentrates U, W, and Sn, and contains negligible structurally bound REE. Abundant, <20 nm-sized uraninite nanoparticles (NPs) are a key host for REE in hematite. In contrast, hematite from mineralized breccias displays co-precipitation of Fe-oxides and REE-minerals facilitated by discharge of high-volatile fluids. Variation in the shape of chondrite-normalized REE fractionation trends for, ranging from concave (hematite containing uraninite NPs) to steeply downwards-sloping (included LREE-dominant phases such as monazite, florencite, fluocerite and cerianite), reflect these differences. Evolving NP mineralogy in the breccias and abundance of monazite reflects successive overprinting events and remobilization of elements from solid-solution and subsequent trapping as NPs via coupled dissolution replacement reaction. REE minerals such as florencite can host nanoinclusions of hematite. Atomic-scale observations, including defects in magnetite and an O-deficient, two-fold hematite superstructure show crystal structural accommodation during Fe-oxide interconversion and inclusion nucleation. Both silician magnetite and hematite show nanoscale sericite forming along planar defects. Understanding the mineralogical deportment of REE at Olympic Dam carries potential implications for investigating the viability of REE extraction opportunities from any resource in which Fe-oxides are the dominant component.